2021
DOI: 10.33119/sd.2021.2.4
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 preventive behaviours among population 50+ in Poland

Abstract: In order to reduce the spread of the SARS-COVID pandemic a set of measures was recommended to reduce the spread of disease and protect individual health. In this article we analyse what factors are associated with utilisation of preventive measures: washing hands, using disinfectant and covering cough among the population of men and women aged 50+. Using Survey of Health, Ageing and Retirement data we estimate logistic regression models for the increased utilisation of each of the preventive behaviours on demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…A survey conducted in the United States found that the older the individuals, the more likely they were to perceive COVID-19 as a significant crisis [11]. However, despite these perceptions and risks, it has been reported that elderly individuals, especially unmarried men, tend to neglect compliance with preventive measures against COVID-19 [12]. Another study found that older adults in Japan also had a lower tendency to use hand sanitizer compared to younger adults [13].…”
Section: Introductionmentioning
confidence: 99%
“…A survey conducted in the United States found that the older the individuals, the more likely they were to perceive COVID-19 as a significant crisis [11]. However, despite these perceptions and risks, it has been reported that elderly individuals, especially unmarried men, tend to neglect compliance with preventive measures against COVID-19 [12]. Another study found that older adults in Japan also had a lower tendency to use hand sanitizer compared to younger adults [13].…”
Section: Introductionmentioning
confidence: 99%